Early Medieval Hoards of Iron Items in Slovenia (Archaeologia Adriatica, 2010)
The article discusses four early mediaeval hoards of iron items in Slovenia. The most complex is the hoard from Sebenje near Bled, which comprises agricultural implements, wood-carving tools, weapons, equestrian equipment and two bucket handles, while the most uniform hoard is from Gradišče above Bašelj, in which equestrian equipment was found. The hoard find from the Ljubljanica River includes, among various tools, an axe-shaped bar, which is a solitary find in Slovenia, whereas in the territories of the Czech Republic, Slovakia and Poland, this type of bar has been found in great numbers and in many hoards. In the hoard from Zidani gaber above Mihovo, agricultural implements were predominant (five sickles and a scythe). The hoards from Slovenian sites have been dated to the period from the 8th to the 10th centuries.
Keywords: axe-shaped bar; Early Middle Ages; hoard; horse equipment; iron implements; tools; weapons